2014
DOI: 10.5152/akd.2014.4775
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of RDW and coronary flow reserve in patient with idiopathic dilated cardiomyopathy

Abstract: Objective: Idiopathic dilated cardiomyopathy (IDC) impairs and reduces coronary flow reserve (CFR). High level of red cell distribution width (RDW) is an independent risk factor for cardiovascular diseases. Therefore, in this observational case-control study we have aimed to determine whether RDW level is associated with CFR impairment in patients with IDC. Methods: We examined 36 patients with IDC and 35 healthy subjects formed as a control group. In addition to this, patients with IDC were divided into two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…To our knowledge, the first time Özülkü et al evaluated the difference in RDW between idiopathic dilated cardiomyopathy with normal versus low coronary flow reserve. 36 They introduced RDW as a powerful predictor of low coronary flow reserve with area under the curve (AUC) of 73% in the receiver operative characteristics (ROC) curve. Another study on patients with dilated cardiomyopathy indicated RDW as a good predictor of long-term mortality and need for transplantation (odds ratio 2.1; 95% confidence interval 1.39–3.23).…”
Section: Rdw and Cardiovascular Diseasesmentioning
confidence: 99%
“…To our knowledge, the first time Özülkü et al evaluated the difference in RDW between idiopathic dilated cardiomyopathy with normal versus low coronary flow reserve. 36 They introduced RDW as a powerful predictor of low coronary flow reserve with area under the curve (AUC) of 73% in the receiver operative characteristics (ROC) curve. Another study on patients with dilated cardiomyopathy indicated RDW as a good predictor of long-term mortality and need for transplantation (odds ratio 2.1; 95% confidence interval 1.39–3.23).…”
Section: Rdw and Cardiovascular Diseasesmentioning
confidence: 99%